Betalain-rich concentrate supplementation improves exercise performance and recovery in competitive triathletes - Montenegro, C. F.; Kwong, D. A.; Minow, Z. A.; Davis, B. A.; Lozada, C. F.; Casazza, G. A. (Applied Physiology, Nutrition, and Metabolism, 2017)
We aimed to determine the effects of a betalain-rich concentrate (BRC) of beetroots, containing no sugars or nitrates, on exercise performance and recovery. Twenty-two (9 men and 13 women) triathletes (age, 38 ± 11 years) completed 2 double-blind, crossover, randomized trials (BRC and placebo) starting 7 days apart. Each trial was preceded by 6 days of supplementation with 100 mg·day-1 of BRC or placebo. On the 7th day of supplementation, exercise trials commenced 120 min after ingestion of 50 mg BRC or placebo and consisted of 40 min of cycling (75 ± 5% maximal oxygen consumption) followed by a 10-km running time trial (TT). Subjects returned 24 h later to complete a 5-km running TT to assess recovery. Ten-kilometer TT duration (49.5 ± 8.9 vs. 50.8 ± 10.3 min, p = 0.03) was faster with the BRC treatment. Despite running faster, average heart rate and ratings of perceived exertion were not different between treatments. Five-kilometer TT duration (23.2 ± 4.4 vs 23.9 ± 4.7 min, p = 0.003), 24 h after the 10-km TT, was faster in 17 of the 22 subjects with the BRC treatment. Creatine kinase, a muscle damage marker, increased less (40.5 ± 22.5 vs. 49.7 ± 21.5 U/L, p = 0.02) from baseline to after the 10-km TT and subjective fatigue increased less (-0.05 ± 6.1 vs. 3.23 ± 6.1, p = 0.05) from baseline to 24 h after the 10-km TT with BRC. In conclusion, BRC supplementation improved 10-km TT performance in competitive male and female triathletes. Improved 5-km TT performances 24 h after the 10-km TT and the attenuated increase of creatine kinase and fatigue suggest an increase in recovery while taking BRC.